Paleoclimatic changes and modulation of East Asian summer monsoon by high-latitude forcing over the last 130, 000 years as revealed by independently dated loess-paleosol sequences on the NE Tibetan Plateau. (1st June 2020) - Li, Guoqiang; Zhang, Haixia; Liu, Xiangjun; Yang, He; Wang, Xiaoyan; Zhang, Xiaojian; Jonell, Tara N.; Zhang, Yunian; Huang, Xin; Wang, Zhong; Yixuan, Wang; Yu, Lupeng; et al.
Abstract: The variability and interaction of the East Asian summer monsoon (EASM) and mid-latitude Westerlies have dominated Eurasian hydroclimates over orbital timescales and currently influence over a billion lives in Asia. Despite this, the mechanisms influencing EASM-Westerlies variability are still a matter of considerable debate. This study presents three loess-paleosol sequences in the NE Tibetan Plateau (NETP) dated at high-resolution by 50 K-feldspar pIRIR and 37 quartz OSL ages to produce the most detailed chronology for any loess record within the plateau. Combined with this chronology are sedimentology, magnetic susceptibility and grain size analyses with TraCE-21ka climatic modelling to constrain atmospheric controls on climatic changes over the NETP during the past 130 kyr. Our results indicate that deposition initiated by ∼130 ka with especially rapid rates during glacial periods, with maximum rates (140–180 g/cm 2 /ka) in early MIS 2. Over interglacial-glacial cycles, NETP climatic changes are consistent with warm-moist interglacial and cold-dry glacial conditions recorded in the monsoonal Chinese Loess Plateau and Westerlies-dominated Central Asia but anti-phase to Central Asia during interglacial and the Holocene substages. These results highlight how variation in EASM intensity strongly controls NETP moisture changes but that Holocene and last interglacial changes recorded in the NETP consistently lag 30°N summer insolation by 2–6 kyr. This study suggests high-latitude forcing effectively modulates EASM intensity and that factors such as ice volume, greenhouse gases, and freshwater input to northern Atlantic and Southern oceans critically influence NETP paleoclimatic conditions. Highlights: K-feldspar pIRIR dating can be used to date loess to at least 130 ka in the Tibetan Plateau. A moist interglacial-dry glacial climate pattern occurred across Eurasia. EASM dominated paleoclimatic changes during past 130 ka in the NE Tibetan Plateau. EASM precipitation is consistently lagged 2–6 ka to July 30°N insolation. High-latitude forcing induced lags in EASM precipitation to insolation.